Four practical revolutions in management : Systems for creating unique organizational capability - Shiba, Shoji; Walden, David (New York Productivity Press, 1993)
This book presents an integrated approach to management aimed at boosting business efficiency and enabling breakthrough opportunities. Shiba and Walden emphasize transforming company thinking to recognize opportunities, even fostering collaboration with competitors. They advocate balancing internal efficiency with outward expansion, especially into emerging Asian markets. The authors promote radical thinking and risk-taking as essential strategies for thriving in a globalized economy.
Includes bibliographical references and index
Keywords: Quản trị kinh doanh